2014
DOI: 10.1007/s11102-014-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysitis: a single-center case series

Abstract: Hypophysitis is an increasingly recognized diagnosis that can present with a broad array of radiographic and clinical features. Surgical biopsy can be helpful to make definitive diagnosis and may guide treatment decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 62 publications
8
49
3
2
Order By: Relevance
“…We found that 65% (90/139) of patients with GTR had headache improvement, higher than the 51% (73/142) of patients with subtotal resection who had headache improvement (P = 0.03). One example of the role of lesional resolution in headache improvement was how none of the five hypophysitis cases with headache had resolution after surgery, which were all biopsies, but four of five improved after a prolonged postoperative course of steroids led to lesional resolution on imaging, as we have described previously [20]. While headache improved more rapidly in patients with headache as a chief complaint (greater improvement at 6 weeks and 6 months, P < 0.05), the long-term improvement rate after 6 months was comparable in the two groups (P > 0.05).…”
Section: Factors Predicting Headache Improvementmentioning
confidence: 57%
“…We found that 65% (90/139) of patients with GTR had headache improvement, higher than the 51% (73/142) of patients with subtotal resection who had headache improvement (P = 0.03). One example of the role of lesional resolution in headache improvement was how none of the five hypophysitis cases with headache had resolution after surgery, which were all biopsies, but four of five improved after a prolonged postoperative course of steroids led to lesional resolution on imaging, as we have described previously [20]. While headache improved more rapidly in patients with headache as a chief complaint (greater improvement at 6 weeks and 6 months, P < 0.05), the long-term improvement rate after 6 months was comparable in the two groups (P > 0.05).…”
Section: Factors Predicting Headache Improvementmentioning
confidence: 57%
“…Recently, an increasing number of clinical studies and patient series have been published [3,5,15,16] . To our knowledge, our paper for the first time describes a series of patients diagnosed with primary autoimmune hypophysitis at a single center in a prospective view.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the recent reports, the frequency of females with primary autoimmune hypophysitis varied from 51.6 to 87.5% [3,[5][6][7][8][9][10][11][12][13][14][15] . In our series, hypophysitis occurred more frequently in female patients, who represented 81% of the cases, with a femaleto-male ratio of approximately 4.3: 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis is confirmed by histopathology and detection of pituitary antibodies (Abs) in patients with isolated or multiple pituitary hormone deficiencies [4] . However, in most cases diagnosis is usually based on endocrinological and radiological findings in the relevant clinical setting [10,11] .…”
mentioning
confidence: 99%